2018
DOI: 10.1186/s13059-018-1519-9
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Genome Browser: a web-based browser for visualizing 3D genome organization and long-range chromatin interactions

Abstract: Here, we introduce the 3D Genome Browser, http://3dgenome.org, which allows users to conveniently explore both their own and over 300 publicly available chromatin interaction data of different types. We design a new binary data format for Hi-C data that reduces the file size by at least a magnitude and allows users to visualize chromatin interactions over millions of base pairs within seconds. Our browser provides multiple methods linking distal cis-regulatory elements with their potential target genes. Users … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
467
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(490 citation statements)
references
References 60 publications
12
467
0
1
Order By: Relevance
“…Chromatin conformation capture assays provide the best evidence for interactions between regulatory elements and target genes. While these assays are cost-prohibitive to run on all samples, data has been generated from an increasing number of diverse cell-types and tissues through individual labs and within the ENCODE consortium that are being compiled and visualized in browsers [96]. In addition, software such as TargetFinder [97] can predict gene targets in specific samples using accessible chromatin data.…”
Section: Opinion: Studies Of Gene×environment×epigenome In Geneticallmentioning
confidence: 99%
“…Chromatin conformation capture assays provide the best evidence for interactions between regulatory elements and target genes. While these assays are cost-prohibitive to run on all samples, data has been generated from an increasing number of diverse cell-types and tissues through individual labs and within the ENCODE consortium that are being compiled and visualized in browsers [96]. In addition, software such as TargetFinder [97] can predict gene targets in specific samples using accessible chromatin data.…”
Section: Opinion: Studies Of Gene×environment×epigenome In Geneticallmentioning
confidence: 99%
“…We confirmed that the hs1150 element is deeply conserved at DNA sequence levels across species. 24 We found that the hs1150 enhancer and OTX2 are in the same TAD ( Figure 1B), suggesting 3D chromatin interactions between hs1150 element and OTX2 transcription unit in the human genome. Cis-acting elements and their regulated genes are usually in topologically associated domains (TADs), and TADs are largely stable across different cell types.…”
Section: Introductionmentioning
confidence: 70%
“…21,22 To assess the regulatory landscape in the OTX2 locus, we examined Hi-C data of H1 human embryonic stem cells 23 using a 3D genome browser. 24 We found that the hs1150 enhancer and OTX2 are in the same TAD ( Figure 1B), suggesting 3D chromatin interactions between hs1150 element and OTX2 transcription unit in the human genome. Collectively, deep conservation across species, reporter expression in transient transgenic mouse embryos at E11.5, and 3D chromatin landscapes of the human genome suggest that the hs1150 element is related to the regulation of OTX2 expression.…”
Section: Introductionmentioning
confidence: 70%
“…Both of these resources feed into the VISION project, which provides raw and normalized data sets selected to cover specific groups of features in mouse and human hematopoiesis, segmentations by integrative modeling (see below), and catalogs of cCREs, among other resources, on the website http://usevision.org. This website includes a link to a genome browser with epigenetic and expression data sets during hematopoiesis as well as the 3D Genome Browser developed by the Yue lab . In addition to the effort to compile and analyze existing data, new data are being generated both within the VISION project and in other laboratories that expand the coverage of epigenetic features across cell types and bring in data sets on new transcription factors or co‐factors.…”
Section: Compile and Determine Epigenetic Features And Transcript Levmentioning
confidence: 99%
“…This website includes a link to a genome browser with epigenetic and expression data sets during hematopoiesis as well as the 3D Genome Browser developed by the Yue lab. 30 In addition to the effort to compile and analyze existing data, new data are being generated both within the VISION project and in other laboratories that expand the coverage of epigenetic features across cell types and bring in data sets on new transcription factors or co-factors.…”
Section: Compile and Determine Epigenetic Features And Transcript Lmentioning
confidence: 99%